Evaluation of Drinking Water Quality in Relation to Body Weight, Feed Efficiency, and Health of Broilers: A Case Study - Rohmad Susilowarno; Elly Tugiyanti; Rosidi Rosidi; Mochammad Sugiarto; Yusmi Nur Wakhidati (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2026)
This study aimed to evaluate the effect of drinking water quality improvement on broiler chicken performance at CV Dua Warna Perkasa. The research employed a comparative observational study design with a pre-post intervention approach, utilizing data collected from three commercial farms before and after the implementation of a comprehensive water quality improvement program. Parameters observed included mortality rate, average body weight (ABW), Feed Conversion Ratio (FCR), Feed Efficiency (FE), and Performance Index (IP). Water quality was assessed through microbiological analysis of samples collected from the source, storage tank, and nipple points, compared against SNI 6488:2019 and Cobb-Vantress 2020 standards. Data were analyzed using descriptive statistics, an independent t-test, and Spearman's correlation. The results showed significant improvements (p < 0.001) in all performance parameters after water quality treatment. Mortality rates decreased from 12.00% to 3.77% in Dendi Farm, 10.61% to 3.49% in Endin Farm, and 13.65% to 3.58% in Noh B Farm. Average body weight (ABW) increased significantly in all farms, while FCR improved from an average of 1.731 to 1.496. The Performance Index showed remarkable improvement from an average of 301 to 449, with Cohen's d effect size of 9.42 (very large). Correlation analysis revealed a very strong relationship between water quality and production performance (Spearman's rho = 0.836-0.867; p < 0.05). The study concludes that water quality management is a critical factor in broiler production efficiency and health maintenance, with significant implications for farm profitability through improved feed efficiency and reduced mortality.